Pengaruh Sukrosa Terhadap Kandungan Total Fenol Minuman Rempah Tradisional (Minuman Secang) - Zulfahmi Zulfahmi; Dwi Eva Nirmagustina (Jurnal Penelitian Pertanian Terapan, 2012)
Secang drink is an Indonesia tradisional drink (from Yogyakarta dan Central Java) there tare made from secang wood (Caesalpia sappan L). In secang drink, we can found another spices, like ginger, clove, sereh, cinnamon bark, kapulaga, and pala. Empirically, the function of secang drink is to take care health, because their bioctive component. The main bioactive component of spices are fenol compound. The fenol compoud can measured with Follin Ciocalteau method. The advantage of Follin Ciocalteau method is give same response to different fenol compound. While the disadvantage is give response to sulfur dioxide and sugar. Except spices, in secang drink contain sugar and salt too, that function to give a delicious taste. The purpose of research is to know the effect of sugar to amount of fenol compoud in secang drink. The amount of fenol compound in secang drink with sugar are 117,972 – 186,055 mg/L. While without sugar are 16,778 – 91,528 mg/L. The incresing of amount of fenol compound in secang drink with sugar because Follin Ciocalteau method to consider sugar is a interference that can give unreal amount of fenol compount. Keywords: sucrose, fenol content, secang drink